Development of an Efficient Bacterial Consortium for the Potential Remediation of Hydrocarbons from Contaminated Sites - Patowary, Kaustuvmani; Patowary, Rupshikha; Kalita, Mohan C.; Deka, Suresh (Frontiers in Microbiology, 2016)
The intrinsic biodegradability of hydrocarbons and the distribution of proficient degrading microorganisms in the environment are very crucial for the implementation of bioremediation practices. Among others, one of the most favorable methods that can enhance the effectiveness of bioremediation of hydrocarbon-contaminated environment is the application of biosurfactant producing microbes. In the present study, the biodegradation capacities of native bacterial consortia towards total petroleum hydrocarbons (TPH) with special emphasis to poly aromatic hydrocarbons (PAHs) were determined. The purpose of the study was to isolate TPH degrading bacterial strains from various petroleum contaminated soil of Assam, India and develop a robust bacterial consortium for bioremediation of crude oil of this native land. From a total of 23 bacterial isolates obtained from three different hydrocarbons contaminated samples 5 isolates, namely KS2, PG1, PG5, R1 and R2 were selected as efficient crude oil degraders with respect to their growth on crude oil enriched samples. Isolates KS2, PG1 and R2 are biosurfactant producers and PG5, R1 are non-producers. Fourteen different consortia were designed involving both biosurfactant producing and non-producing isolates. Consortium 10, which comprises two Bacillus strains namely, Bacillus pumilus KS2 and Bacillus cereus R2 (identified by 16s rRNA sequencing) has shown the best result in the desired degradation of crude oil. The consortium showed degradation up to 84.15% of total petroleum hydrocarbon (TPH) after five weeks of incubation, as revealed from gravimetric analysis. FTIR (Fourier transform infrared) and GCMS (Gas chromatography-mass spectrometer) analyses were correlated with gravimetric data which reveals that the consortium has removed a wide range of petroleum hydrocarbons in comparison with abiotic control including different aliphatic and aromatic hydrocarbons.